Re-signifying the past: monuments, decoloniality and resistance in Latin American public space (Tempo e Argumento, 2025)
Monuments in Latin America have been key tools in constructing collective memories and power relations, consolidating official narratives that exclude subaltern voices. This study examines their resignification as a means of resistance and democratization of public space, addressing exclusion dynamics and the need to include historically marginalized perspectives. It explores emblematic cases, such as interventions during the Chilean social uprising, highlighting actions of critical redefinition and the ethical and political challenges of building an inclusive collective memory. It is concluded that monuments must be turned into living devices that engage with contemporary needs.
Keywords: monuments; collective memory; resignification; public space; Latin America